PERBEDAAN JUMLAH BAKTERI COLIFORM PADA 3 JENIS ES BATU (ES BATU KEMASAN PLASTIK, ES KRISTAL, DAN ES BALOK) - EKO NANING SOFYANITA (Jurnal Health Sains, 2023)
The Ice cubes have a very low temperature, this is an assumption that the ice cubes consumed are relatively safe, even though coliformbacteria at that temperature do not necessarily die. Coliformis a bacterium that is used as an indicator of water contamination. Research Objectives comparing Coliform bacteria in ice cubes (plastic packaging, ice crystals, ice cubes) sold in the Peterongan market. This research is an observational study with descriptive research criteria through a cross sectional approach. All samples of 15 ice cubes consisting of plastic packaged ice cubes, ice crystals, ice blocks sold at the Peterongan Market, Semarang city 6 samples (5, 8, 2, 6, 14, 15) did not meet the requirements set by the Agency National Standardization No. SNI 388:2009 regarding maximum limit of microbial and food contamination is 3/gramMPN index. This is caused by hygiene and sanitation factors such as not providing water for washing hands and washing utensils, poor waste handling, unhygienic serving of ice cubes. In addition, the water factor is the raw material for ice cubes which is not clean and is not cooked first Samples of ice cubes sold by beverage traders at the Peterongan market, Semarang City were all found to contain Coliform bacteria.